(untitled) (Nordic Journal of Practical Theology, 2023)
The Christian spiritual practice called ‘centering prayer’ is growing in popularity internationally, and today it is also offered by some congregations in Church of Norway. However, compared to the vast literature on resemblant forms of spirituality, like mindfulness and meditation, there is a scarcity of research on centering prayer. With this study, we seek to make this lacuna a bit smaller. More specifically, we want to shed light on the participants’ experiences of centering prayer in comparison to regular church services. Our material combines qualitative and quantitative data. In the analysis, we combine inductive and theory-driven approaches. One of our main findings is that the participants’ experiences of centering prayer is more overlapping with experiences of Sunday services than we expected. Our findings challenge Woodhead and Heelas´ influential theory of a discrepancy between ‘religion’ and ‘spirituality’. These findings also challenge commonly shared conceptions of what ‘authenticity’ means in spiritual life.